(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Contemporary Cuban writer Zoé Valdés is recognized as an author who offers resistance to dictatiorship through her literary work. One of the main characteristics of her prose is her focus on female characters, Eros, and corporeality. In this paper, thematization of female corporeality and sexuality in the novel Café Nostalgia is therefore explored, primarily through the analysis of the love and sexual experiences of the protagonist, Marcela, a Cuban woman in Paris, who is also the narrator. In her examination of her own identity and her story of youth in Cuba, episodes marked by trauma, violence, abortion, and sexual transgressions stand out as important for analysis. The theoretical framework of the research is primarily based on the erotical reflections thoughts of Georges Bataille, as well as on reflections of Michel Foucault, Mikhail Naumovich Epstein and Roland Barthes. We pay particular attention to the relationship between eroticism and transgression, as well as the significance of sexual transgression as a form of rebellion against the ideology of Fidel Castro’s regime. By exploring the thematization of corporeality and sexuality in the novel Cafe Nostalgia, we have shown that the female body can be understood as a kind of political body, as it preserves traces of the context in which it is located, but at the same time represents a subject that offers resistance to phallocentrism and Castro’s ideology. Through the analysis of episodes from Marcela’s life, we have come to the insight that her sexuality is determined both by trauma and violence, as well as by a significant degree of transgression. Every transgression and every crossing of the border of heteronormative sexuality represents a challenge to the Castro’s ideology. In this sense, we have highlighted the scene of the orgy, which is transgressive through the violation of monogamy as the only acceptable form of sexual relations, through homosexuality, but also through the inappropriateness of the presence of a child-voyeur. Also, the research shows that Zoé Valdés thoughtfully shapes the erotographic elements in the narrative and that they sum up the complex relationships that are built between eros, trauma, transgressiveness and violence. In this sense, we paid special attention to the final scene - the scene of erotic cannibalism, which represents the moment in which the main character dissolves her own traumas and experiences sexual liberation. The aim of this paper was to highlight the significance of this type of female literature, to provide an analysis of eroticographic elements, and to show the female sexual body as a political body that has the potential to undermine the phallocentric regime.